2015
DOI: 10.1530/erc-15-0013
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant of MDM4 influences regulation by multiple microRNAs in prostate cancer

Abstract: The oncogene MDM4, also known as MDMX or HDMX, contributes to cancer susceptibility and progression through its capacity to negatively regulate a range of genes with tumoursuppressive functions. As part of a recent genome-wide association study it was determined that the A-allele of the rs4245739 SNP (AOC), located in the 3 0 -UTR of MDM4, is associated with an increased risk of prostate cancer. Computational predictions revealed that the rs4245739 SNP is located within a predicted binding site for three micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 50 publications
3
67
1
Order By: Relevance
“…Although risk assessments are not directly comparable to survival analysis, our findings may seem somewhat contradictory to the report of the SNP34091A allele as a risk factor for recurrence and tumor-related death in ovarian cancer patients [20]. While the SNP34091A allele has been reported to confer higher MDM4 levels in ovarian [20] and prostate cancer cells [19], and the common assumption is that the oncogenic effect of high MDM4 levels is through the p53 pathway [31], it has been reported that over 90 % of all HGSOC have mutations in the TP53 gene [32]. Thus, it may be that the effect of MDM4 SNP34091 on ovarian cancer risk is mediated via additional pathways, other than p53.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Although risk assessments are not directly comparable to survival analysis, our findings may seem somewhat contradictory to the report of the SNP34091A allele as a risk factor for recurrence and tumor-related death in ovarian cancer patients [20]. While the SNP34091A allele has been reported to confer higher MDM4 levels in ovarian [20] and prostate cancer cells [19], and the common assumption is that the oncogenic effect of high MDM4 levels is through the p53 pathway [31], it has been reported that over 90 % of all HGSOC have mutations in the TP53 gene [32]. Thus, it may be that the effect of MDM4 SNP34091 on ovarian cancer risk is mediated via additional pathways, other than p53.…”
Section: Discussioncontrasting
confidence: 85%
“…Further, they reported the SNP rs1563828T allele, which is in LD with the SNP34091A allele among Caucasians, to be associated with early onset of both familial and sporadic ovarian cancer [16]. To the best of our knowledge, the biological effects of SNP rs1563828 have not been elucidated; thus, the possibility exist that it may be SNP34091, which is known to have a biological effect [19, 20], that contributes to the observed effect of SNP rs1563828 previously reported by Atwal and colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a single nucleotide polymorphism (SNP) in the 3′ untranslated region of the MDM4 gene, rs4245739 A > C has been found to affect MDM4 mRNA stability and protein levels [4]. Genotype AA was recorded to be more frequent in patients with high-grade than low-grade ovarian carcinoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale analysis of genetic variants in miRNA binding sites identified 22 prostate cancer risk associated miRSNPs, the 2 most significant miRSNPs being KLK3 (kallikrein related peptidase 3) rs1058205 (TϾC) and VAMP8 (vesicle associated membrane protein 8) rs1010 (AϾG), which were targeted by miR-3162-5p and miR-370 -5p respectively in an allele specific manner (77 ). Similarly, the C allele of the rs4245739 SNP (AϾC) located in the 3ЈUTR of the MDM4 (MDM4 p53 regulator) oncogene is a target of miR-191-5p and miR-887 resulting in prostate cancer protection (78 ). Therefore, in addition to miRNA expression profiles, cancer diagnosis and therapeutics may rely on the presence of miRSNPs in either precursor miRNAs, mature miRNAs or in 3Ј UTRs of miRNA target genes.…”
Section: Mirnas In Anticancer Therapymentioning
confidence: 99%